Stroke Rehabilitation: Should Physiotherapy Intervention be Provided at a Primary Health Care Centre or the Patients’ Place of Domicile? (2014)
"Purpose: This randomized controlled trial compared the outcomes of physiotherapy intervention on selected indices of recovery for stroke survivors treated at a primary health centre group (PHCG) with those treated in their respective places of domicile group (DG). Methods: Participants were 52 individuals comprising 24 males and 28 females who had suffered a stroke and were recently discharged from two inpatient health facilities in Ibadan, Nigeria. They were randomly assigned into either the PHCG (n=25) or DG (n = 27) and treated twice weekly for 10 consecutive weeks using a physiotherapy intervention protocol comprising a battery of task- specific exercises. The outcomes measured were motor function, balance and handicap assessed using the modified motor assessment scale (MMAS), short-form postural assessment scale for stroke (SF-PASS) and reintegration to normal living index (RNLI), respectively, as well as walking speed which was assessed using a standard technique. Results: Between-group comparison using the General Linear Model revealed no statistically significant difference in both the pre- and post-intervention scores of the two groups on the MMAS, SF-PASS, RNLI and walking speed in both PHCG and DG (p>0.05). However, within-group comparison yielded a statistically significant difference in each of the indices of stroke recovery measured across the 10-week period in both groups. Conclusion: Physiotherapy intervention at the primary health care centre and respective homes of stroke survivors similarly improved clinical outcomes. Treatment at any of these locations may enhance access to physiotherapy after stroke in a low- income community like Nigeria. "